Determination of Natural Radioactivity in Some Commercial Motor Oil Samples - Ahmed, Firas Hashem; Karim, Mahmood Salim; Darwoysh, Hassan Hadi; Mansour, Hazim Louis (Al-Nahrain Journal of Science, 2019)
In this paper, the measurement of specific activity concentrations of five commercial oil samples obtained from different countries (Kuwait, U.A.E., Iran, and Germany) were carried out using (HPGe) detector. From the measurement it was observed that average values of specific activity concentrations for 238U, 232Th and 40K were equal to (20.206±1.4 Bq/l), (20.080±3.5 Bq/l) and (162.120±49.2Bq/l), respectively. The results were less than their corresponding recommended global values reported by (UNSCEAR, 1994) publication. The radiation hazard indices [Iɣ, Hin, Hex, Raeq, DƔ, (AEDE)in and(AEDE)out] were also studied, and all the obtained results and their average value were also observed to be lower than their corresponding average values given by (UNSCEAR,1994, 2000). Finally, the excess life time cancer risk (outdoor), (ELCR), results were found to be ranged from 0.102´10-3 (Al-Khaleej) (Kuwaiti origin) sample to 0.147´10-3 (Vulcan 330) (Iranian origin) sample, with an average value of (0.121±0.012)´10-3, which were less than the world average value. Thus, the results of the present work have shown that, all the studied samples of motor oil are safe when used.